Inventory Management of Unrepeat Production: Case Study of Pot Meets Pop Denim - Abirafdi, Muhammad; Basri, Mursyid Hasan (Journal of Business and Management, 2012)
Pot Meets Pop (PMP) is a fashion company which specialist in jeans product. PMP is one the pioneer of jeans business in Indonesia. Now, PMP have more than 20 articles of product for the latest season. 70% of lineup product is a jeans product like bottoms and jackets. PMP vision is to be a business leader in Indonesia and South East Asia. To reach the goal, PMP have to increase overall performance such as production planning and marketing advertising.Â The methodology of this research use primary data which came from direct observation and secondary data which got from another source such as text book and internet. Direct observation already done in PMP office, story, and authorized store. All the research data would be gathered find the best solution for PMP problem. This research only use bottoms jeans product as an object to limiting the object research.Based on root causes analysis, there are four major problems; less market knowledge, advertising promotion, inventory recording, and forecast method. This study aims to solve the problem and find a solution for each problem.After processing data analysis has been done, the solution for every problem has found. The solution for 4 problems; software for inventory record, create advertising and promotion, all staff have to join the forum, and forecasting methods.After giving a solution to PMP, it needs to be implemented in PMP activity for forecasting and marketing. The solution will help PMP to improve overall performance of PMP.Keywords: Pot Meets Pop, Forecast, Fashion Industry, Business Process, Root Cause Analysis, Inventory Management.